Exploring Learning Motivation Through Contextual Learning in ESP Classes: A Study on Automotive Engineering Students - Yeni Rahmawati; Septianto, Adit; Khatimah, Khusnul (Borneo Educational Journal (Borju), 2025)
This research investigated how contextual learning influences students’ motivation and English proficiency in English for Specific Purposes (ESP) classes for automotive engineering students. Motivated by the disconnect between general English curricula and students’ vocational goals, this research applies contextual strategies aligned with the ARCS motivational model—Attention, Relevance, Confidence, and Satisfaction. A total of 91 students participated, and data were collected using a validated questionnaire. Statistical analyses, including Cronbach’s alpha (0.851), descriptive statistics, t-tests, and multiple regression, were used. The findings reveal that contextual learning significantly enhances students’ motivation, especially in the areas of relevance and attention, and contributes positively to their English language performance. Regression analysis showed that motivational factors explained 18.1% of the variance in English proficiency scores, with “Relevance” emerging as the strongest predictor. Students reported higher satisfaction and engagement when learning materials reflected their professional context. This research confirms that integrating real-world content into ESP instruction not only improves student motivation but also supports linguistic outcomes. These results advocate for ESP curricula that are closely tied to industry-related content to better equip vocational students for future professional demands.